Radiotherapy treatment delays and their influence on tumour control achieved by various fractionation schedules. - Wyatt, R; Jones, B; Dale, R (2008)
There is often a considerable delay from initial tumour diagnosis to the start of radiotherapy treatment. This paper extends the calculations of a previous paper on the effects of delays before the initiation of radiotherapy treatment to include results from a variety of practical fractionation regimes for three different types of tumour: squamous cell carcinoma (head and neck), breast and prostate. The linear quadratic model of radiation effect, logarithmic tumour growth (coupled with delay times where relevant) and the Poisson model for tumour control probability (TCP) are used to calculate the change in TCP for delays between diagnosis and treatment. Within the limitations of radiobiological modelling, these data can be used to tentatively assess the interactions between delays, dose fractionation and TCP. The results show that delays in the start of radiotherapy treatment do have an adverse effect on tumour control for fast-growing tumours. For example, calculations predict a reduction in local tumour control of up to 1.5% per week's delay for head and neck cancers treated following surgery. In addition, there may be a variety of fractionation regimes that will yield very similar clinical results for each tumour type. It is shown theoretically that, for the tumour types considered here, it is possible to increase the dose per fraction and decrease the number of fractions while maintaining or increasing TCP relative to standard 2 Gy fractionation regimes, although there may be some advantage to using hyperfractionated regimes for head and neck cancers in order to reduce normal tissue effects.